Features of personal and professional self-realization of teaching and learning psychologists - Katkalo, Ksenia D. (Saratov State University, 2023)
The relevance of the research is determined by the increasing role of a teaching and learning psychologist in the educational process, as well as the need for a teaching and learning psychologist to meet the requirements of the modern education system. The purpose of the research is to study the types of personal and professional self-realization of teaching and learning psychologists, as well as the psychological predictors of such self-realization. The article puts forward the hypothesis that there are characteristic types of personal and professional self-realization of teaching and learning psychologists, whose predictors are the parameters of the motivational and semantic sphere, and instrumental and stylistic characteristics of the personality, as well as indicators of self-regulation and emotional stability. Participants: teaching and learning psychologists (N=164) of educational institutions in Yekaterinburg and the Sverdlovsk region, including women (N = 150) and men (N = 14), aged 25 to 60 years; 32.4% have job experience of more than 10 years, 23.2% – from 5 to 10 years, 44.4% – less than 5 years. Methods (tools): Multidimensional Questionnaire of Personality Self-realization (S. I. Kudinov) was used to identify the features of self-realization of teaching and learning psychologists, Life Orientations Test (D. A. Leontiev) was used to identify the parameters of the motivational and semantic sphere, Resilience Test (E. N. Osin, E. I. Rasskazova) and Questionnaire of Volitional Self-control (A. G. Zverkov, E. V. Eidman) were used to study instrumental and stylistic characteristics and indicators of emotional stability, the technique of professional identity analysis (L. B. Schneider) was used to assess the parameters of professional development. Life Satisfaction Scale (E. Dinner adapted by D. A. Leontiev, E. N. Osin) and diagnostic methods of subjective well-being of the individual (R. M. Shamionov, T. V. Beskova) were used to assess the success of personal and professional self-realization. Results: the research has identifi ed the characteristic types of personal and professional self-realization of teaching and learning psychologists diff ering in the degrees of manifestation of its structural components: “positive”, “negative”, “imaginary” and “prospective”. Based on the three general factors: “life awareness”, “active life position” and “crisis of professional development”, the author has suggested the empirically confi rmed models of how psychological characteristics and types of personal and professional self-realization of teaching and learning psychologists are interrelated. The article also describes the predictors of personal and professional self-realization of teaching and learning psychologists. Main conclusions: the article has clarifi ed the features of personal and professional self-realization of teaching and learning psychologists as subjects of educational relations; additionally, the study has identifi ed the role of personal characteristics (motivational-semantic, instrumental-stylistic, emotional, resource) in achieving personal and professional self-realization, when the latter is the foundation of the subjective well-being and life satisfaction of teaching and learning psychologists in the conditions of modern transformations in the education system. The results of the study can be used to develop programs for personal and professional development, prevention of crises of professional development, psychological support of teaching and learning psychologist at diff erent stages of their professional paths and personal growth.